Estrogen receptors in nonfunctioning pituitary neuroendocrine tumors: review on expression and gonadotroph functions - Haydar Ali Tajuddin, Amalina; Kamaruddin, Norazmi; Sukor, Norlela; Azizan, Elena Aisha; Omar, Ahmad Marzuki (Oxford University Press, 2020)
Estrogen (17β-estradiol or E2) is a crucial regulator of the synthesis and secretion of pituitary reproductive hormones luteinizing hormone, follicle-stimulating hormone, and prolactin. In this review, we summarize the role of estrogen receptors in nonfunctioning pituitary neuroendocrine tumors (NF-Pitnets), focusing on immunoexpression and gonadotroph cell proliferation and apoptosis. Gonadotroph tumors are the most common subtype of NF-Pitnets. Two major estrogen receptor (ER) isoforms expressed in the pituitary are estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ). Overall, estrogen actions are mostly exerted through the ERα isoform on the pituitary. The G protein–coupled estrogen receptor (GPER) located at the plasma membrane may contribute to nongenomic effects of estrogen. Nuclear immunoreactivity for ERα and ERβ was highest among gonadotroph and null cell tumors. Silent corticotroph tumors are the least immunoreactive for both receptors. A significantly elevated ERα expression was observed in macroadenomas compared with microadenomas. ERα and ERβ may act in opposite directions to regulate the Slug- E-cadherin pathway and to affect invasiveness of NF-Pitnets. In the cellular pathway, ERs regulate estrogen-induced proliferation and differentiation and impact several signaling pathways including the MAPK and PI3K/Akt pathway. Estrogen was the first-discovered inducer of pituitary tumor transforming gene 1 that was abundantly expressed in NF-Pitnets. ERα can be a potential biomarker for predicting tumor size and invasiveness as well as therapeutic target for NF-Pitnets. Selective estrogen receptor modulators or antiestrogen may represent as an alternative choice for the treatment of NF-Pitnets.